The association between visceral fat and blood pressure in adults - JM, Hamid Jan; Z, Hafidah; Mohd Zainuddin, Laila Ruwaida; Isa, Nur Firdaus; KP, Jayah; WM, Wan Manan (Universiti Sains Malaysia, Kubang Kerian, 2011)
This cross-sectional study investigates the association between body composition measurements and blood pressure in Malay adults. A total of 296 adults, aged between 18 to 59 years, consisting of 122 males and 174 females underwent measurements of weight and height, waist and hip circumference, body fat and visceral fat, and blood pressure. Body fat and visceral measurements were carried out through bioelectric impedance, using a portable Tanita body fat analyser. Bivariate correlation analysis was used to study the association of each body composition measurement with blood pressure. There was significant association between Body Mass Index (BMI) (r= 0.25, P<0.01), waist circumference (r= 0.27, P<0.01), hip circumference (r= 0.20, P<0.01) and visceral fat (r= 0.29, P<0.01) with blood pressure, respectively. No significant relationship was found between waist hip ratio (WHR) and total body fat with blood pressure. The association between visceral fat and blood pressure is an interesting finding with regards to this community research setting. It is important to further study the affordability, accuracy and application of bioelectrical impedance technology in community research.